SEDATIVE EFFECT OF CLARY SAGE (SALVIA SCLALAREA, L) ON MICE USING AN OLFACTORY AROMATHERAPY - Idajani Hadinoto; Engkun Kuswono; Ani Marlina; Anna Setiawati (Indonesian Journal of Pharmacy, 2001)
A research has been conducted to study the sedative effect of the Clary sage oil (Salvia sclaria, L), using an olfactory aromatherapy method, on male white mice, which have been tested using rotarod, platform and chimney tests. Clary sage oil was given to the male white mice in three different exposed times : 0.5, 1, and 1.5 hours. As a reference standard was used diazepam 170 ug/kg body weight (intraperitoneal). The research indicates that the administration of Clary sage oil can indeed cause the sedative effect. There is also a correlation between the exposure time of Clary sage oil and the sedative effect observed. Key-words : sedative effect, clary sage oil, olfactory aromatherapy